Functional neurological symptoms: Optimising efficacy of inpatient treatment and preparation for change using the Queen Square Guided Self‐Help. Issue 2 (9th July 2021) - Humblestone, Susan; Roelofs, Jacob; Selai, Caroline; Moutoussis, Michael
Abstract: Objective: Functional neurological symptoms (FNS) are disabling symptoms without macro‐structural cause. While inpatient treatment confers important benefits, it is resource‐intensive, and hence, it is important to optimise its efficiency. Methods: We developed a brief, Internet‐based preparatory therapy based on psychoeducation and CBT, termed the Queen Square Guided Self‐help (QGSH), to maximise the efficacy of the inpatient FNS treatment at the National Hospital for Neurology and Neurosurgery. Results: The QGSH aims to ensure that prior to admission, the patient understands (a) the diagnosis of FNS, (b) the five‐areas CBT model and (c) the use of goal setting in rehabilitation. It has now run since 2017, and 191 patients have taken part in the inpatient FNS programme, with 122 of these having participated in the QGSH. It runs for up to 12 weeks and includes original videos and patient worksheets, as well as signposting to existing published resources. Information is sent weekly by email, and content is delivered in the form of 11 modules built around online video sessions. Conclusion: We believe that the set of materials used in QGSH has the potential to benefit patients with FNS and can support clinicians wishing to develop their expertise. It could help with the development of new FNS services, and we are in the process of developing it into a stand‐alone service. We hope that the experience of the Queen Square team can be used to help patients and clinicians to improve the provision of FNS services.